Development of the Taruna Melati Utama Paripurna Cadre Training Module Based on the Experiential Learning Method at PP IPM - Khadijah Hairani; Dirgantara Wicaksono (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study develops a Training Module for Taruna Melati Utama Paripurna Cadres (PKPTMU) using Experiential Learning at the Central Board of Ikatan Pelajar Muhammadiyah (PP IPM). Using a research and development method with the ADDIE model, the study involved facilitators, the cadre development division, and PKPTMU participants. Expert validation results indicate that the module is valid (media: 3.75; material: 3.80), while small- and large-group trials scored 3.74 and 3.81, respectively (both categorized as very good). The N-Gain analysis shows an improvement in learning outcomes from the medium to the high category. More than 85% of participants rated the module as engaging and relevant, confirming its feasibility and effectiveness for cadre development.